Nursing care at end of life: a UK-based survey of the deaths of people living in care settings for people with intellectual disability. (September 2019) - Northway, Ruth; Todd, Stuart; Hunt, Katherine; Hopes, Paula; Morgan, Rachel; Shearn, Julia; Worth, Rhian; Bernal, Jane
Background: People with intellectual disability are believed to be at risk of receiving poor end-of-life care. Nurses, given their advocacy role and duty to provide compassionate end-of-life care, have the potential to change this situation but research regarding this aspect of their role is limited. Aims: This paper thus seeks to answer the question 'How and when are nurses involved in providing care at end of life for people with intellectual disability?' Methods: A total of 38 intellectual disability care providers in the UK providing support to 13, 568 people with intellectual disability were surveyed. Data regarding 247 deaths within this population were gathered in two stages and subsequently entered into SPSSX for analysis. Results: Findings revealed that the majority of deaths occurred between the ages of 50 and 69 years, the most commonly reported cause of death being respiratory problems. Both community and hospital-based nurses were involved in supporting individuals during their final 3 months of life, and sometimes more than one type of nurse provided support to individuals. Generally nursing care was rated positively, although room for improvement was also identified. Conclusions: Nurses are involved in supporting people with intellectual disability at end of life and appropriate education is required to undertake this role. This may require change in curricula and subsequent research to determine the impact of such change on nursing support to this population.